2011
DOI: 10.1038/leu.2011.184
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of stem and progenitor cells in cardiovascular diseases

Abstract: Circulating bone marrow (BM)-derived stem and progenitor cells (SPCs) participate in turnover of vascular endothelium and myocardial repair after acute coronary syndromes. Acute myocardial infarction (MI) produces a generalized inflammatory reaction, including mobilization of SPCs, increased local production of chemoattractants in the ischemic myocardium, as well as neural and humoral signals activating the SPC egress from the BM. Several types of circulating BM cells were identified in the peripheral blood, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 114 publications
2
70
0
Order By: Relevance
“…The mobilization of BM-derived stem cells (BM-SCs) in patients with acute MI is considered a reparatory response, [21][22][23][24] and experimental studies have suggested an important role of BMSCs in cardiac repair response after MI. 13,20,[24][25][26][27][28][29] Nevertheless, the contribution of circulating cells to myocardial and endothelial repair is still incompletely understood. Moreover, the mobilization of endothelial progenitor cells correlates with the ischemic zone and not with the necrotic zone of patients after MI, 30 suggesting the possibility of an active mechanism originating from the ischemic border zone of the heart that is transmitted to the BM.…”
Section: Mobilization and Homing Of Bm Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mobilization of BM-derived stem cells (BM-SCs) in patients with acute MI is considered a reparatory response, [21][22][23][24] and experimental studies have suggested an important role of BMSCs in cardiac repair response after MI. 13,20,[24][25][26][27][28][29] Nevertheless, the contribution of circulating cells to myocardial and endothelial repair is still incompletely understood. Moreover, the mobilization of endothelial progenitor cells correlates with the ischemic zone and not with the necrotic zone of patients after MI, 30 suggesting the possibility of an active mechanism originating from the ischemic border zone of the heart that is transmitted to the BM.…”
Section: Mobilization and Homing Of Bm Progenitor Cellsmentioning
confidence: 99%
“…20,31 It is possible that ischemic tissue releases these chemoattractants, which create a gradient directing the cells to the site of injury. This mechanism was aptly demonstrated in vitro by positive migration of BM-SCs expressing early cardiac markers toward the homogenates of infarcted mouse myocardium enriched with stromal-derived factor-1, hepatocyte growth factor, and leukemia inhibitory factor.…”
Section: Mechanism Of Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging question is whether inflammatory processes in the infarct zone promote or inhibit cell engraftment. On the one hand, inflammation acts as an activating factor for cell homing and proliferation via the production of chemoattractants (chemokines, cytokines, bioactive lipids; Cui and Madeddu, 2011;Ratajczak et al, 2012;Wojakowski et al, 2012) as well as complement activation (Ratajczak et al, 2012). On the other hand, a hostile microenvironment may impair cell engraftment, survival and differentiation (Swijnenburg et al, 2010;Sheikh et al, 2012).…”
Section: Duration Of Action Homing and Retentionmentioning
confidence: 99%
“…Investigation on the role of circulating angiogenic cells in CVD is complicated by the large heterogeneity of cells with direct and indirect pro-angiogenic capacities (117). Indeed, this pool includes CD34 + progenitor cells, Tie2 expressing monocytes, and mesenchymal stem cells (MSCs) from bone marrow (BM) and non-BM sources (26).…”
Section: Introductionmentioning
confidence: 99%